Domain state modulation by interfacial diffusion in FePt/FeCo thin films: experimental approach with micromagnetic modelling. (28th June 2021) - Vashisht, Garima; Hussain, Zainab; Sulania, Indra; Ojha, Sunil; Reddy, V R; Annapoorni, S
Abstract: We report the complex implications of inter-diffusion between polycrystalline FePt/FeCo layers as an impact of the FeCo underlayer on the structural and magnetic properties of the system. The crystalline growth of FePt strongly reduces in an entirely diffused system compared to the one with lesser diffusion, while the crystalline structure of FeCo is apparently less affected. Charge redistribution occurs between Fe, Co and Pt ensuring increased Co–Pt and Fe–Pt interactions with higher diffusion. Thereafter, we combine hysteresis and magnetic force microscopy measurements to show that the interfacial deformations result in the distinct out-plane magnetic behaviour of the system. FeCo@FePt nano-composite like structure, originating due to interfacial diffusion, shows interactions between two magnetic phases with in-plane low anisotropy exhibiting wasp-shaped out-plane hysteresis loop. Whereas the layered structure of FePt/FeCo films shows random anisotropy with a significant out-plane contribution even in the polycrystalline films. Micromagnetic modelling demonstrates coercivity deterioration and reduction of switching field due to the formation of a slightly diffused interface. Contrarily, the experimental observations for complete diffusion between the two layers are explained by simulating the inhomogeneous distribution of anisotropies along the film plane. These studies provide deep perceptions of the magnetic properties of FePt/FeCo system governed by diffusion kinetics which are valuable to achieve desired magnetic characteristics using this system.